Impaired cardiorespiratory coupling in young normotensives with a family history of hypertension. Issue 11 (November 2018) - Xie, Lin; Li, Mengjun; Dang, Shijie; Li, Chaomin; Wang, Xiaoni; Liu, Binbin; Mei, Mengqi; Zhang, Jianbao
Abstract : Objectives: Although recent animal studies have highlighted the importance of cardiorespiratory coupling in the pathogenesis of hypertension, little research has assessed the cardiorespiratory coupling in humans at high risk of developing hypertension. The aim of this study was to investigate the cardiorespiratory coupling in healthy young individuals genetically predisposed to hypertension at both rest and mental stress conditions. Methods: We studied 39 normotensive male participants [21 with (FH+) and 18 without (FH−) a family history of hypertension]. Electrocardiography, impedance cardiography, beat-to-beat blood pressure and respiratory signal were simultaneously recorded during 5 min of rest and 5 min of mental arithmetic task (MAT). Stroke volume, cardiac output, systemic vascular resistance, baroreflex sensitivity and aortic pulse wave velocity were calculated. Autonomic activity was approximated noninvasively by the spectral analysis of cardiovascular variability. Respiratory sinus arrhythmia (RSA) and cardiorespiratory phase synchronization (CRPS) were used to define the amplitude and phase relationships of cardiorespiratory coupling. Results: All resting parameters were similar between FH− and FH+ groups except resting CRPS, which was lower in FH+ group. Furthermore, the changes in hemodynamic parameters and cardiovascular variability at MAT were comparable in FH− and FH+ groups. Moreover, MAT elicited a decrease in CRPS of FH− group, whereas CRPS of participants in FH+ group remained unchanged during MAT. Conclusion: Healthy offspring of hypertensive parents have lower CRPS at rest, indicating an early impairment of cardiorespiratory coupling. Furthermore, CRPS decreased under mental stress in participants without a family history of hypertension, whereas this reactivity of CRPS was absent in participants with a family history of hypertension.